The Role of BSO El-Abbasy in Arabic Learning at Universities - Fatma Horsan; Khizanatul Hikmah (Indonesian Journal of Islamic Studies, 2022)
This study aims to describe the role of BSO El-Abbasy Umsida in Arabic Learning for PBA Umsida students and to find out the problems faced by BSO El-Abbasy. This research is a qualitative descriptive study, the techniques used to collect data are direct and open observation techniques, unstructured interviews, and documentation. And in this study using data analysis techniques developed by Miles and Huberman, namely data reduction, data presentation, and drawing conclusions. The results showed that, 1) The role of El-Abbasy BSO in Arabic Learning for Umsida PBA Students, including: a). Hold Arabic language course classes, b). Arabic debate training, c). Inform the competition. 2) The problems faced by BSO El-Abbasy in Learning Arabic for Umsida PBA Students are: a). The minimum number of students taking Arabic courses, b). Lack of student motivation in participating in competitions, c). Lack of teaching staff at BSO El-Abbasy d). The debate training only runs when there will be a competition.